2016
DOI: 10.1128/iai.00519-16
|View full text |Cite
|
Sign up to set email alerts
|

The Life Cycle Stages of Pneumocystis murina Have Opposing Effects on the Immune Response to This Opportunistic Fungal Pathogen

Abstract: P neumocystis species are opportunistic fungal pathogens that cause severe pneumonia in immunocompromised hosts, including AIDS patients. Clearance of Pneumocystis organisms is dependent on effective CD4ϩ T and B cell and macrophage responses (1-4). Failure to clear Pneumocystis organisms leads to severe alveolar damage due to the exaggerated inflammatory immune response (5). In spite of a reduced incidence of Pneumocystis pneumonia (PcP) in HIV-infected individuals due to improved antiviral therapies, the mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(49 citation statements)
references
References 40 publications
2
47
0
Order By: Relevance
“…The counter-regulatory generation of anti-inflammatory IL-1Ra release mediated by Mincle receptors and not previously reported during PCP, may, on one hand represent a means to limit lung tissue damage during infection, but may also represent an important mechanism through which Pneumocystis species persist in the lung environment by dampening the host responses to infection. Indeed, recently Garvy et al demonstrated that the trophic life cycle forms of Pm suppress β-glucan induced proinflammatory cytokine responses, associated with the β-glucan rich Pm cysts wall (68). It will be interesting in future studies to determine if Pneumocystis trophic forms might actively modulate anti-inflammatory immune cytokines such as IL-1Ra as a mechanism to persist and propagate in the host.…”
Section: Discussionmentioning
confidence: 99%
“…The counter-regulatory generation of anti-inflammatory IL-1Ra release mediated by Mincle receptors and not previously reported during PCP, may, on one hand represent a means to limit lung tissue damage during infection, but may also represent an important mechanism through which Pneumocystis species persist in the lung environment by dampening the host responses to infection. Indeed, recently Garvy et al demonstrated that the trophic life cycle forms of Pm suppress β-glucan induced proinflammatory cytokine responses, associated with the β-glucan rich Pm cysts wall (68). It will be interesting in future studies to determine if Pneumocystis trophic forms might actively modulate anti-inflammatory immune cytokines such as IL-1Ra as a mechanism to persist and propagate in the host.…”
Section: Discussionmentioning
confidence: 99%
“…These cells play a crucial role in recognising, binding and initiating the CD4 + T cell host response to Pneumocystis . While the type of cell that primes a T-cell in response to Pneumocystis is important, a recent study has also highlighted that the form of organism affects the host response to infection [31]. In contrast to the ascus, the trophic form lacks a cell wall and therefore innate cells respond poorly with reduced CD4+ T-cell recruitment and IFNγ production [32].…”
Section: The Role Of Cell-mediated Adaptive Immunitymentioning
confidence: 99%
“…The Pneumocystis inoculum used was purified by differential filtration as we reported to remove host related debris (Kottom et al, 2017). We utilised intratracheal instillation to insure that each mouse received comparable organism inoculation load, and such intratracheal instillation has been used to study host responses to Pneumocystis (Evans, Bryant, & Garvy, 2016; Hoy et al, 2020; Rapaka et al, 2010). For the immunocompetent infection model, mice were sacrificed at 20 days after infection (Kottom et al, 2018).…”
Section: Methodsmentioning
confidence: 99%